N-Octanoyl dopamine transiently inhibits T cell proliferation via G1 cell-cycle arrest and inhibition of redox-dependent transcription factors. Issue 3 (13th June 2014) - Wedel, Johannes; Hottenrott, Maximillia C; Stamellou, Eleni; Breedijk, Annette; Tsagogiorgas, Charalambos; Hillebrands, Jan-Luuk; Yard, Benito A
Abstract : N-octanoyl dopamine displays transient T cell suppressive activity by preventing NFκB and AP-1 activation, and acts synergistically with calcineurin inhibitors on T cell proliferation. Abstract: Recently, we developed a nonhemodynamic dopamine derivative, NOD, which has profound anti-inflammatory effects in vitro. As NOD also protects rats from ischemic AKI, the present study tested whether NOD is able to modulate cellular immunity for potential use as a T cell-suppressive agent. To this end, T cells were stimulated by anti-CD3/CD28 or PMA/ionomycin in the presence or absence of different concentrations of NOD. T cell proliferation, activation markers, intracellular cytokine expression, and activation of transcription factors were assessed. Whereas T cell proliferation was inhibited significantly by NOD at Day 3, proliferation was restored at Day 7 or later depending on the NOD concentration used. Inhibition of proliferation was reflected by a diminished CD25 expression and switch from naive to memory T cells. Early TCR activation events were unaffected, yet NF-κB and AP-1 were strongly inhibited by NOD. The inhibitory effect of NOD seemed to be dependent on its redox activity, as NOT, a redox-inactive NOD derivate, did not influence proliferation. NOD displayed synergistic effects with CNIs on T cell proliferation. Our data demonstrate that NOD displays T cell-suppressive activity. In keeping with its anti-inflammatory action and its beneficial effect on ischemia-induced AKI, NOD may be an interesting drug candidate to prevent CNI-related side-effects.